Forming professional skills of students at art-graphic departments - Кудренко, Дар’я (Pedagogy of Higher and Secondary Education, 2014)
Kudrenko D. О. Forming professional skills of students at art-graphic departments. The article reveals the concept of “professional skills” and “competence” of students at art-graphic departments in the context of the fine arts, decorative and applied activity. The author defines a set of professional skills that are compulsory for students of art-graphic departments in implementating professional activity.